Fabrication, testing and evaluation of mechanical properties of woven glass fibre composite material. (2018) - nandaragi, Sanjeev R; Reddy, Babu; Badari Narayana, K
Abstract: Fiber reinforced composites are finding increasing application due to their high specific strength and stiffness to weight ratios. In some special cases, customized components/ structures are produced by different combination of reinforcements and matrix materials in different orientations. For other applications where weight is considered as paramount instead of its strength or stiffness, a special class of composite namely woven fiber composites is employed. As a student, understanding the complete cycle of a composite system starting from the selection of materials, design of necessary mold, manufacture simple composite panel / system using handmade process, preparing test coupons for finding its tensile, compressive and bending properties as per standards and finally realizing the validity of numbers obtained through the test process is considered to be very exciting. In the present work, woven glass fiber composites with epoxy resin are considered. The orientation of glass fabric considered is 0 0 /45 0 /0 0 /45 0 /0 0 (no specific motive in selecting this particular orientation). The woven fiber composite sheets are prepared by hand-lay-up method. Few test specimens are made in order to find their mechanical properties such as tensile, compressive and bending strengths as per ASTM standards. This paper describes the manufacturing, development of test specimens, testing process and the results obtained for a woven glass fiber composite material.